2012
DOI: 10.3354/cr01058
|View full text |Cite
|
Sign up to set email alerts
|

Near-future climate change over Europe with focus on Croatia in an ensemble of regional climate model simulations

Abstract: The RegCM climate model was used at a 35 km resolution to downscale the 3-member global ECHAM5/MPI-OM ensemble based on the IPCC A2 scenario covering the EuropeanMediterranean domain. Within the reference climate (1961−1990), the model high 2 m temperatures (T2m) were reduced and low temperatures were increased relative to verification in a large portion of the domain. Precipitation was underestimated in summer over the Mediterranean region but was overestimated over western Europe in winter, probably due to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Gao et al (2012), in particular, completed a 1950-2100 scenario simulation, showing that the temperature change signal is mostly determined by large-scale conditions, while the precipitation change signal is strongly modulated by fine-scale topographical forcing. Similar conclusions, although with smaller signals, are found in the 35 km grid spacing near term climate scenario ex periments over a European domain by Branković et al (2012). They also focused on the simulation of extremes, showing that a very high resolution is indeed needed to reproduce observed statistics of the most intense precipitation events.…”
Section: Contributions To This Climate Specialsupporting
confidence: 72%
“…Gao et al (2012), in particular, completed a 1950-2100 scenario simulation, showing that the temperature change signal is mostly determined by large-scale conditions, while the precipitation change signal is strongly modulated by fine-scale topographical forcing. Similar conclusions, although with smaller signals, are found in the 35 km grid spacing near term climate scenario ex periments over a European domain by Branković et al (2012). They also focused on the simulation of extremes, showing that a very high resolution is indeed needed to reproduce observed statistics of the most intense precipitation events.…”
Section: Contributions To This Climate Specialsupporting
confidence: 72%
“…Significant progresses have been made on the climate projections for the Mediterranean region (Branković et al 2012, Vautard et al 2013, Lionello et al 2014. Study of Giorgi (2006) showed that the most responsive region to clim atic change is Mediterranean followed by the North Eastern European regions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1f,j with h,l). Such an underestimation of summer precipitation over southern Europe is found to be a persistent deficiency in several generations of RCMs (Hagemann et al ., 2004; Kotlarski et al ., 2014; Ceglar et al ., 2015; Prein et al ., 2015a; Giot et al ., 2016) and in particular over the Adriatic region (Branković et al ., 2012, 2013). The resolution increase yields a reduction of precipitation errors over the northern parts of CRO in the ERA‐Interim runs; however, this is less obvious in simulations when RegCM4 is forced by GCMs.…”
Section: Resultsmentioning
confidence: 99%